Cassirers politische Philosophie Zwischen allgemeiner Kulturtheorie und Totalitarismus-Debatte - Parkhomenko, Roman (KIT Scientific Publishing, 2007)
The paper presents the main lines of the European totalitarianism debates to demonstrate Cassirer's argument on the same phenomenon of totalitarianism. The author focuses on Cassirer's philosophy of culture and political philosophy in relation to the above mentioned debate.